2020
DOI: 10.3892/mmr.2020.11145
|View full text |Cite
|
Sign up to set email alerts
|

Integrated microarray analysis to identify potential biomarkers and therapeutic targets in dilated cardiomyopathy

Abstract: dilated cardiomyopathy (dcM) is a primary cardiomyopathy with high mortality. The aim of the present study was to identify the related genes in dcM. The four expression profiles (GSE17800, GSE21610, GSE42955 and GSE79962) downloaded from the Gene Expression Omnibus (GEO) database were analyzed using RankProd and metaMA R packages to identify differentially expressed genes (DEGs). DEGs were uploaded to the Database for Annotation, Visualization and Integrated Discovery (DAVID), for Gene Ontology (GO) and Kyoto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Calumenin can also relieve ER stress-initiated apoptosis in viral myocarditis [ 20 ]. Recently, Zhang et al [ 33 ] identified that calumenin was downregulated in dilated cardiomyopathy. In this study, our results revealed that calumenin levels were decreased in the RV of PAH mice and miR-335-5p antagomir could rescue the downregulation of calumenin, indicating that miR-335-5p might regulate RV remodeling via calumenin.…”
Section: Discussionmentioning
confidence: 99%
“…Calumenin can also relieve ER stress-initiated apoptosis in viral myocarditis [ 20 ]. Recently, Zhang et al [ 33 ] identified that calumenin was downregulated in dilated cardiomyopathy. In this study, our results revealed that calumenin levels were decreased in the RV of PAH mice and miR-335-5p antagomir could rescue the downregulation of calumenin, indicating that miR-335-5p might regulate RV remodeling via calumenin.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia was excluded by coronary angiography. 15) Subjects with poor compliance, incomplete clinical data, contrast agent sensitivity, and autoimmune diseases were excluded. Additionally, subjects with obvious surgical contraindications were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13] Based on this approach, a series of genes and pathways are found to be associated with the prediction and prognosis of dilated cardiomyopathy. 14,15) In addition, studies have shown that immune cell infiltration plays an important role in the occurrence and development of various diseases. 16) For instance, some studies have found biomarkers in patients with acute myocardial infarction 17) or in those with atrial fibrillation with valvular heart disease based on immune cell infiltration.…”
mentioning
confidence: 99%
“…Recently, the link between iron overload and cardiovascular disease was attributed to ferroptosis [29,30]. Ferroptosis is an iron-dependent form of programmed cell death involving lipid hydroperoxide accu-mulation [31]. Both in-vitro and in-vivo evidence supports the pathophysiological role of ferroptosis on many forms of cardiovascular dysfunctions [32].…”
Section: Introductionmentioning
confidence: 99%